Low level direct interpolation for parametric curves (1998)
We present an algorithm for the direct interpolation of parametric curves with a CNC machine -- The algorithm expresses parametric planar curves as sequences of discrete axes movements of BLU size of the machining tool -- Therefore, the curve C(u) is directly approximated by the pulse trains, hence eliminating one source of the machining errors